Assessing drivers of maize storage losses in south west Benin using a fractional response model. (September 2019) - Ogoudedji, Sylvie A.; Egyir, Irene S.; Osei-Asare, Yaw; Seini, Al-Hassan Wayo; Honlonkou, Albert
Abstract: An assessment of drivers of maize storage losses was undertaken in south west Benin applying the Fractional Response Model on information collected from 400 smallholder maize farmers. The mean loss of maize during the storage period reported by farmers was estimated at 10.25 percent of the total harvest. The average marginal effect obtained from the fitted Fractional Response Model revealed that storage technologies, farmers' post-harvest attitudes, insect damage, weather conditions and infrastructures play a significant role in storage losses maize farmers experience in south west Benin. The findings revealed that farmers who used bags and plastic containers respectively reduced storage losses by 6.7 and 7.8 percentage points compared to farmers who used woven granary baskets. The results also indicated that applying ash, neem leaves, pepper or lemon increased the storage loss by 4.11 percentage points compared to storing without protectant. Drying after harvesting decreased the storage loss by 1.9 percentage point. In contrast, the storage loss increased by 5.1 percentage points for respondents who reported insects as predators of their stored maize, and by 2.1 percentage points when it rains at the time of maize harvest. A one-degree increase in temperature was associated with an increase in storage losses of 4.4 percentage points and farmers who live at less than 26.09 km to market reduced storage losses by 0.17 percentage point. Effective policies for a sustainable reduction of storage losses among maize farmers in the area should consider the need to raise awareness about the loss issue that represents the use of woven granary basket, ash, neem leaves, pepper and lemon as storage technologies. Farmers should be informed to avoid harvesting during times of rain, encouraged to properly dry their produce after harvesting and sustainable hermetic equipment robust against insect growth during storage should be promoted. Highlights: Farmers lose more than 10% of their maize harvest during storage in south west Benin. Maize drying after harvest and the hermetic characteristic of storage equipment are critical in reducing storage losses. Woven granary baskets are associated with an increase in storage losses. There is a need to raise awareness about the loss issue that represents the use of woven granary baskets for storage. Sustainable hermetic equipment robust against insect growth during storage should be promoted in south west Benin.